2016
DOI: 10.2139/ssrn.2839800
|View full text |Cite
|
Sign up to set email alerts
|

Animal Spirits, Fundamental Factors and Business Cycle Fluctuations

Abstract: We explore empirically the role of noisy information in cyclical developments to separate fluctuations due to genuine changes in fundamentals from those driven by temporary animal spirits (or noise shocks). Exploiting the fact that the econometrician has a richer dataset in some dimensions than the consumers, we use a novel identification scheme in a structural VAR framework and show that noise shocks are important drivers of business cycle fluctuations. In particular, noise shocks play a large role in consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Dées and Guntner (2014), Levchenko and Pandalai-Nayar (2015)), ex-post measures of economic developments (e.g. Dées and Zimic (2016)) or survey-based nowcast errors (e.g. Enders et al (2013)), the results are heterogeneous and remain sensitive to the model setup and assumptions made.…”
Section: Literature On Confidencementioning
confidence: 99%
See 1 more Smart Citation
“…Dées and Guntner (2014), Levchenko and Pandalai-Nayar (2015)), ex-post measures of economic developments (e.g. Dées and Zimic (2016)) or survey-based nowcast errors (e.g. Enders et al (2013)), the results are heterogeneous and remain sensitive to the model setup and assumptions made.…”
Section: Literature On Confidencementioning
confidence: 99%
“…They also find supportive evidence for the notion of a confidence channel in the international transmission of shocks. Dées and Zimic (2016) Temporary animal spirits/false news (noise shock) vs. News…”
Section: Dées and Guntner (2014)mentioning
confidence: 99%
“…6 In contrast, Starr (2012) found a positive, small, and significant effect of sentiment on spending after filtering out shifts in sentiment due to exogenous shifts in news coverage. Similarly, Blanchard et al (2013), Dées and Zimic (2019), and Öztürk and Stokman (2019) showed that animal spirit exists and may have a considerable impact on spending growth in Europe and the United States.…”
Section: Introductionmentioning
confidence: 96%
“…Dées y Zimic (2016). En la teoría keynesiana, el determinante fundamental de la inversión son las expectativas sobre los rendimientos futuros de esta (cuyas oscilaciones son el fruto de los animal spirits).5 Véase, entre otros, Durante, Ferrando y Vermeulen (2020).…”
unclassified